Um sistema baseado em perfil e recomendação para suporte à governança corporativa - Dal Molin, Rafael (2017)
In today's scenario, high competition and demanding consumers, it is essential that companies, regardless of size, seek techniques and tools to enable better management. When we talk about management, especially in this turbulent period, a major problem that comes in mind is how to determine if the company is doing well and what aspects could be improved. In this sense, the performance indicators are fundamental to measure with clear measures of company performance in accordance with the information requirements imposed by the administration. So any company, of any size, structure or segment can use different types of indicators to track their activities and thus measure the consequences of their decisions in business management. Performance indicators are indices developed within each company, according to its reality andfocusing on the main points that affect not only its management and its organizational result, but analyze the development of the strategy. There are indicators for different areas, according to many methods: financial ratios, operational, market, time, and other costs. The objective is to create a software for profile analysis of companies. This analysis will take place through the collection of information at the operational level of ERP systems. The information is stored in a single database where indices and calculations will be applied to generate performance indicators, and these are the basis for the construction of profiles. From the analysis of these profiles, it is proposed to carry out recommendations for corrective action or application of goals to improve the organization's performance in question.